Race and identity: An Analysis of Lacanian Lack Approaches to Burnt Shadows (Journal of Asian Development Studies, 2025)
This study employs Lacanian psychoanalysis—especially the constitutive notion of lack—to examine how Kamila Shamsie's Burnt Shadows unsettles racial identity across imperial and post 9/11 geographies. By foregrounding the psychic mechanics of racialization, the study bridges psychoanalysis and postcolonial race critique. Scholarship on Shamsie emphasises trauma and transnationalism, but offers no sustained Lacanian account of racial subjectivity. (1) how racist ideology functions in the novel's social and intimate scenes; (2) how lack and desire mediate racial identity formation. Close readings of pivotal episodes (Nagasaki's aftermath; Delhi and Karachi displacements; Cold War Berlin; post-9/11 New York) paired with Lacanian concepts—symbolic order, objet petit a, fantasy, enjoyment—track patterns of interpellation and misrecognition. Recurrent misreading of bodies, name changes, accent shifts, and border encounters form a pattern in which subjects seek the Other's approval while disavowing constitutive lack; textual evidence shows fantasy suturing racial incoherence yet repeatedly failing to do so. Racist ideology operates through enjoyment and prohibition to fix subjects in racial positions, but Shamsie's narrative exposes their contingency, rendering race fluid, relational, and historically wounded. The study reframes racial identity as a negotiated psychic formation shaped by history and law, offering a portable analytic for postcolonial fiction. The abstract narrows the scope to racial subjectivity, clarifies the theoretical lexicon, and specifies scenes as evidentiary anchors to strengthen coherence and replicability.